Fluid-regulatory hormone responses during cycling exercise in acute hypobaric hypoxia - Bocqueraz, O.; Koulmann, N.; Guigas, B.; Jimenez, C.; Melin, B. (Medicine & Science in Sports & Exercise, 2004)
Purpose: This study was designed to describe the responses of fluid-regulating hormones during exercise in acute hypobaric hypoxia and to test the hypothesis that they would be dependent on the relative intensity of exercise rather than the absolute workload. Methods: Thirteen men cycled for 60 min on four occasions in the same individual hydration status: in normoxia at 55% and 75% of normoxia maximal aerobic power (N55 and N75, respectively), in hypoxia (PB = 594 hPa) at the same absolute workload and at the same relative intensity as N55 (H75 and H55, respectively). [latin capital V with dot above]O2, heart rate, and rectal and mean skin temperatures were recorded during exercise. The total water loss was measured by the difference in nude body mass adjusted for metabolic losses. Venous blood samples were drawn before and 15, 30, 45, and 60 min after the beginning of exercise to measure variations in plasma volume, osmolality, and concentrations in arginine vasopressin (AVP), atrial natriuretic factor (ANF), plasma renin activity (ARP), aldosterone (Aldo), and noradrenaline (NA). Results: During N55 and H55, AVP, Aldo and ARP did not change, whereas ANF increased slightly. Increases in AVP, Aldo, ARP, and NA were greater during N75 than during H75, whereas the increase in ANF was greater during H75 than N75. Conclusion: Plasma levels of AVP, Aldo, and ARP increase during exercise when a threshold is reached and thereafter are dependent on the absolute workload, without any specific effect of hypoxia. The time course of ANF appears to be different from that of the other hormones.